The Effect of Work Environment, Workload and Information Technology on Employee Performance - Nurhaliza, Nada Lia; Titi Rapini; Sri Hartono (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Employee performance is one of the factors that greatly influences the work system, be it an organization or company, and whether a company or organization is good or not can be seen from how good or bad the performance of the employees is. The purpose of this study is to determine the role of independent variables in the form of work environment, workload and information technology on employee performance by taking the object of research at Surya Mart Supermarket Ponorogo. This research uses quantitative research principles. The data used in the research data mining process are primary data and secondary data. The parties selected as the population are employees of Surya Mart Supermarket Ponorogo with a sample of 45 people. The summary of the research results is that the work environment variable has a positive effect on employee performance variables, the workload variable has a positive effect on employee performance, and the information technology variable is positive on employee performance simultaneously, all variables affect employee performance.